From Mendel to genomics, plant breeding milestones: a review - Borém, Aluízio; Guimarães, Elcio Perpétuo; Federizzi, Luiz Carlos; Toledo, José Francisco Ferraz de (Crop Breeding and Applied Biotechnology, 2002)
Plant breeding has evolved from an intuitive strategy of choosing the best plants in the field to an excitingscience of combining genes to improve desirable traits. Our objective with this paper is to review some of themost important discoveries and developments that had an impact on plant breeding. First, we present backgroundinformation and then the milestones themselves. The topics were grouped into chapters to facilitate comprehensionof their contribution to plant breeding. They are discussed within each chapter in a plant-breeding-orientedchronological way. When applicable, the definition, importance and evaluation of the topics are presented
Keywords: Genetics history; Plant improvement; Heredity; Biotechnology; Retrospective